Greece : 2018 Article IV Consultation and Proposal for Post-Program Monitoring-Press Release; Staff Report; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report, 2018)
Greece has stabilized its economy and begun to grow. The authorities deserve credit for largely eliminating macroeconomic imbalances, including via a significant fiscal adjustment, and for many other reforms undertaken in recent years. Reflecting these efforts, European partners have provided significant support, most recently agreeing to a final loan disbursement under the ESM program and additional debt relief. However, as the country exits the program era in August, crisis legacies and an unfinished policy reform agenda in most areas weigh on Greece's prospects. High public debt, weak bank balance sheets, reliance on capital controls and emergency liquidity assistance, and worrisome social indicators, including still-high unemployment, all weigh on growth and social cohesion. Fiscal adjustment has been sizable, but has relied on distortionary high tax rates on still-narrow bases and growth-detrimental discretionary spending cuts, and efforts to bring down tax and spending arrears have been met with limited success. Social spending is better targeted, but many social needs remain unmet and the risk of poverty remains high. Bank credit continues to shrink. Structural reform efforts to address obstacles to growth and competitiveness-while significant-have fallen wellshort of what is needed, and competitiveness indicators remain below the Euro Area average. Notably, the planned reversal of reforms to the collective bargaining framework risks undoing previous gains in competitiveness.